Composition for preparing a passivation layer and a passivation layer using the same
A composition of fluoroolefin, vinyl ether, silane, and epoxide compounds with an adhesion promoter forms a passivation layer with low dielectric constant and water absorption, addressing the limitations of existing layers by improving adhesion and pattern formation in electronic devices.
Patent Information
- Application Number
- JP2021544212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-28
- Filing Date
- 2020-01-28
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2040-01-28
AI Technical Summary
Existing passivation layers in microcircuit electronic devices fail to simultaneously achieve low dielectric constant, low water absorption, and excellent adhesion to the adhered surface, as exemplified by Korean Patent Application Publication No. 10-2018-0044790 (A) and International Publication No. 2017-136266 (A1).
A composition comprising a fluoroolefin compound, a vinyl ether compound, a silane compound with an alkenyl group, and an epoxide compound, along with a fluorocopolymer and an adhesion promoter, is used to form a passivation layer that is crosslinkable, enhancing adhesion and pattern formation while maintaining low dielectric constant and water absorption.
The passivation layer exhibits excellent adhesion, pattern formability, low dielectric constant, and low water absorption, making it suitable for applications in thin film transistors, organic field effect transistors, and various electronic devices.
Smart Images

Figure 0007611150000001 
Figure 0007611150000002 
Figure 0007611150000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for producing a passivation layer that simultaneously exhibits commercially desirable effects such as low dielectric constant, low water absorption, excellent pattern formability, and excellent adhesion to a substrate, and to a passivation layer formed from the composition. [Background technology]
[0002] In various electronic devices, certain coating layers are applied as electrically insulating materials to protect the devices from damage by physical and chemical means and from moisture.
[0003] For this reason, certain coating layers are used as passivation layers for microcircuit electronic devices. The usefulness is greatly increased if the polymers used to form such passivation layers are photocrosslinkable to form polymer patterns with defined small dimensions to provide a three-dimensional framework for the interconnection of multiple electronic components, circuits and layers. As the characteristics of electronic devices trend toward smaller size, shift to higher frequencies and lower power consumption, polymers such as polyimides that were traditionally used in the past cannot meet the new stringent requirements for low dielectric constant, low loss tangent, and low water absorption.
[0004] Korean Patent Application Publication No. 10-2018-0044790(A) and International Publication No. 2017-136266(A1) disclose a passivation layer, but the passivation layers disclosed therein have low dielectric constants and water absorption rates but low adhesion to the adherend surface.
[0005] Therefore, there is an urgent need to develop a composition for producing a passivation layer that can simultaneously exhibit effects such as a low dielectric constant, low water absorption, excellent pattern formability, and excellent adhesion to the surface to be bonded. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Korean Patent Application Publication No. 10-1996-0009050(A) (1996.03.22) Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made to solve the above-mentioned problems, and aims to provide a composition for producing a passivation layer, which simultaneously exhibits effects such as low dielectric constant, low water absorption, excellent pattern formability, and excellent adhesion to the adherend surface, and a passivation layer formed using the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In order to achieve the above object, the present invention provides a composition for producing a passivation layer, comprising a fluorocopolymer, which is a random copolymer of monomers including a fluoroolefin-based compound, a vinyl ether-based compound, a crosslinkable compound selected from the group consisting of a silane-based compound having at least one alkenyl group, and an epoxide-based compound having at least one alkenyl group, and an adhesion promoter.
[0009] According to one embodiment of the present invention, the fluoroolefin-based compound includes a compound represented by the following formula 1, the vinyl ether-based compound includes a compound represented by the following formula 2, and the crosslinkable compound includes a silane-based compound having at least one alkenyl group represented by the following formula 3:
[0010] [ka]
[0011] In formula 1, R 1is a linear perfluoroalkoxy group having 1 to 5 carbon atoms, a branched perfluoroalkoxy group having 3 to 5 carbon atoms, a linear perfluoroalkyl group having 1 to 3 carbon atoms, H, F, or Cl;
[0012] In formula 2, R 2 is a linear alkyl group having 1 to 6 carbon atoms, a branched alkyl group having 3 to 6 carbon atoms, a cyclic alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted aryl group;
[0013] In formula 3, R 3 is an ethylenically unsaturated hydrocarbon group, and R 4 is an aryl, an aryl-substituted hydrocarbon group, a branched alkoxy group, a substituted or unsubstituted cyclic alkoxy group, a branched alkyl group, or a substituted or unsubstituted 5- or 6-membered cyclic alkyl group; R 5 and R 6 is independently selected from a linear or branched alkoxy group, or a substituted or unsubstituted cyclic alkoxy group. 3 is an ethylenically unsaturated hydrocarbon group having 2 to 5 carbon atoms, R 4 is an aryl, an aryl-substituted hydrocarbon group, a branched alkoxy group having 3 to 6 carbon atoms, a substituted or unsubstituted 5- or 6-membered cyclic alkoxy group, a branched alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted 5- or 6-membered cyclic alkyl group; R 4 and R 5 is independently selected from a straight or branched chain alkoxy group having 1 to 6 carbon atoms, or a substituted or unsubstituted 5- or 6-membered cyclic alkoxy group.
[0014] In another embodiment of the present invention, the fluoroolefin-based compound includes a compound represented by the following formula 1, the vinyl ether-based compound includes a compound represented by the following formula 2, and the crosslinkable compound includes an epoxide-based compound having at least one alkenyl group represented by the following formula 4:
[0015] [ka]
[0016] In formula 1, R 1 is a linear perfluoroalkoxy group having 1 to 5 carbon atoms, a branched perfluoroalkoxy group having 3 to 5 carbon atoms, a linear perfluoroalkyl group having 1 to 3 carbon atoms, H, F, or Cl;
[0017] In formula 2, R 2 is a linear alkyl group having 1 to 6 carbon atoms, a branched alkyl group having 3 to 6 carbon atoms, a cyclic alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted aryl group;
[0018] In formula 4, R 7 is an alkenyl group having 2 to 5 carbon atoms, or a group of the formula -R 8 -OC(=O)-CR 9 ═CH2, where R 8 is an alkylene group having 1 to 5 carbon atoms, R 9 is hydrogen or methyl.
[0019] In one embodiment, the adhesion promoter comprises a thiol-based compound. In one embodiment, the thiol-based adhesion promoter is selected from the group consisting of sulfur-functional carboxylic acids, sulfur-functional alcohols, and sulfur-functional silanes. Examples of thiol-based adhesion promoters include 3-(triethoxysilyl)propanethiol (MPTES), 6-mercapto-1-hexanol, 3-mercaptopropionic acid, 11-mercapto-1-undecanol, and 3-(trimethoxysilyl)propanethiol (MPTMS).
[0020] In one embodiment, the adhesion promoter comprises a diol-based compound. In one embodiment, the diol-based adhesion promoter is selected from the group consisting of 1,n-hydrocarbon diols (n is 2 to 6) and alkyl-substituted 1,2-benzenediols. Examples of diol-based adhesion promoters include 4-tert-butylbenzene-1,2-diol, hexane-1,6-diol, and 1,3-butylene glycol.
[0021] In one embodiment, the adhesion promoter comprises a first adhesion promoter comprising a thiol-based adhesion promoter as described above, and a second adhesion promoter comprising a diol-based adhesion promoter as described above.
[0022] In one embodiment, the weight ratio of the first adhesion promoter to the second adhesion promoter is 1:0.5 to 3.5.
[0023] In one embodiment, the composition comprises 0.5 to 3.5 parts by weight of the adhesion promoter based on 100 parts by weight of the fluorocopolymer.
[0024] In one embodiment, the composition may further comprise 0.1 to 5 parts by weight of a photoacid generator (PAG) based on 100 parts by weight of the fluorocopolymer.
[0025] In one embodiment, the composition may further comprise 150 to 450 parts by weight of a solvent, based on 100 parts by weight of the fluorocopolymer.
[0026] In one embodiment, the composition may further comprise 0.05 to 5 parts by weight of a photosensitizer (PS) based on 100 parts by weight of the fluorocopolymer.
[0027] The present invention further provides a passivation layer comprising a layer of a crosslinked coating composition disposed on an outer surface of a semiconductor device, the coating composition comprising any of the compositions for making a passivation layer of the above-mentioned embodiments, the composition comprising a fluorocopolymer which is a random copolymer copolymerized by including a crosslinkable compound selected from the group consisting of a fluoroolefin-based compound, a vinyl ether-based compound, a silane-based compound having at least one alkenyl group, and an epoxide-based compound having at least one alkenyl group as a monomer, and an adhesion promoter.
[0028] According to one embodiment of the present invention, at least a portion of the passivation layer may be developed to form a predetermined pattern.
[0029] In some embodiments, the exterior surface of the semiconductor device onto which the passivation layer is coated comprises at least one substrate selected from the group consisting of conductive materials, semiconductive materials, and non-conductive materials. In some embodiments, the exterior surface of the semiconductor device comprises at least one substrate selected from the group consisting of glass, polymer, inorganic semiconductor, organic semiconductor, tin oxide, zinc oxide, titanium dioxide, silicon dioxide, indium oxide, indium zinc oxide, zinc tin oxide, indium gallium oxide, indium gallium zinc oxide, indium tin zinc oxide, cadmium sulfide, cadmium selenide, silicon nitride, gold, copper, and aluminum.
[0030] In some embodiments of a passivation layer comprising a layer of a crosslinked coating composition disposed on an exterior surface of a semiconductor device, the area that peels off in an adhesion evaluation measured by Measurement Method 1 below may be less than 6% of the lattice area, the dielectric constant measured at a frequency of 1 MHz in accordance with ASTM D150 may be 2.65 or less, and the water absorption measured by Equation 1 below may be 0.15% or less.
[0031] Measurement method 1 The passivation layer of the Au substrate on which the passivation layer has been formed is cross-cut so that there are 100 graduations at 1 mm intervals, and the adhesion is evaluated in accordance with ASTM D3359.
[0032] equation 1 Water absorption rate (%)=((W2-W1) / W1)×100(%) Here, W1 is the weight of the passivation layer before being left for 24 hours under conditions of a temperature of 85°C and a relative humidity of 85%, and W2 is the weight of the passivation layer after being left for 24 hours under conditions of a temperature of 85°C and a relative humidity of 85%.
[0033] Effect of the Invention The passivation layer formed using the composition according to the present invention can simultaneously exhibit effects such as a low dielectric constant, a low water absorption rate, excellent pattern formability, and excellent adhesion to the adherend surface, and can therefore be widely applied to various articles such as thin film transistors, organic field effect transistors, semiconductors, semiconductor oxide field effect transistors, integrated circuits, light emitting diodes, bank layers containing organic light emitting diodes, display devices, printed circuit boards, and photovoltaic devices.
[0034] Mode of invention In the present specification, some embodiments will be described in detail so that those skilled in the art can easily implement the embodiments. However, the embodiments are not limited to those described below, and various modifications are possible.
[0035] A composition for producing a passivation layer according to one embodiment of the present invention comprises a fluorocopolymer, which is a random copolymer of monomers including a fluoroolefin-based compound, a vinyl ether-based compound, and a crosslinkable compound selected from the group consisting of a silane-based compound having at least one alkenyl group and an epoxide-based compound having at least one alkenyl group, and an adhesion promoter.
[0036] First, the fluorocopolymer will be described.
[0037] The fluorocopolymer is a random copolymer of monomers including a fluoroolefin-based compound, a vinyl ether-based compound, and a crosslinkable compound selected from the group consisting of a silane-based compound having at least one alkenyl group and an epoxide-based compound having at least one alkenyl group.
[0038] The fluoroolefin-based compound may include a compound represented by the following formula 1:
[0039] [ka]
[0040] In formula 1, R 1 may be a linear perfluoroalkoxy group having 1 to 5 carbon atoms, a branched perfluoroalkoxy group having 3 to 5 carbon atoms, a linear perfluoroalkyl group having 1 to 3 carbon atoms, H, F, or Cl. 1 may be a linear perfluoroalkoxy group having 1 to 3 carbon atoms, a branched perfluoroalkoxy group having 3 carbon atoms, a perfluoroalkyl group having 1 carbon atom, F, or Cl.
[0041] The fluoroolefin compound may be contained in an amount of 39 to 60 mol %, preferably 41 to 58 mol %, and more preferably 44 to 55 mol %, based on the total amount of repeating units of the monomers constituting the fluorocopolymer.
[0042] Furthermore, the vinyl ether compound may contain a compound represented by the following formula 2.
[0043] [ka]
[0044] In formula 2, R 2may be a straight chain alkyl group having 1 to 6 carbon atoms, a branched alkyl group having 3 to 6 carbon atoms, a cyclic alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted aryl group.
[0045] The substituted aryl group may be an aryl group in which at least one hydrogen atom on the aromatic ring is substituted, or may be one or more alkylphenyl, halophenyl, or aminophenyl groups selected from the group consisting of tolyl, xylyl, and -C6H4(CH2CH3).
[0046] The vinyl ether compound may be contained in an amount of 39 to 60 mol %, preferably 41 to 58 mol %, and more preferably 44 to 55 mol %, based on the total amount of repeating units of the monomers constituting the fluorocopolymer.
[0047] In one embodiment of the crosslinkable compound, the crosslinkable compound is a silane-based compound having at least one alkenyl group represented by the following formula 3.
[0048] [ka]
[0049] In one embodiment of the present silane-based compound having at least one alkenyl group, in formula 3, R 3 is an ethylenically unsaturated hydrocarbon group, and R 4 is an aryl, an aryl-substituted hydrocarbon group, a branched alkoxy group, a substituted or unsubstituted cyclic alkoxy group, a branched alkyl group, or a substituted or unsubstituted 5- or 6-membered cyclic alkyl group; R 5 and R 6 is independently selected from a straight chain or branched alkoxy group, or a substituted or unsubstituted cyclic alkoxy group.
[0050] In a preferred embodiment of the silane-based compound of the present invention having at least one alkenyl group, in formula 3, R 3is an ethylenically unsaturated hydrocarbon group having 2 to 5 carbon atoms, R 4 is an aryl, an aryl-substituted hydrocarbon group, a branched alkoxy group having 3 to 6 carbon atoms, a substituted or unsubstituted 5- or 6-membered cyclic alkoxy group, a branched alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted 5- or 6-membered cyclic alkyl group; R 4 and R 5 is independently selected from a straight or branched chain alkoxy group having 1 to 6 carbon atoms, or a substituted or unsubstituted 5- or 6-membered cyclic alkoxy group.
[0051] In this preferred embodiment of the silane-based compound of the present invention having at least one alkenyl group, in formula 3, R 4 is selected to be a relatively sterically bulky substituent attached to the silicon atom of the silane-based compound, which allows the formation of a fluorocopolymer composition (e.g., a solution) having a phase-stable shelf life of 3 months or more without special precautions, without undesirable gel formation due to silicon-oxygen bridges (-Si-O-Si-) due to hydrolysis or the like at room temperature. For example, R 4 The aryl group in may include phenyl and naphthyl groups, and the aryl-substituted hydrocarbon group is, for example, an alkyl group having 1 to 3 carbon atoms and substituted with an aryl group, for example, an alkyl group in which at least one hydrogen atom is replaced with an aryl group, such as -CHCH-phenyl. 4 may be a branched alkoxy group having 3 to 6 carbon atoms, such as isopropoxy, isobutoxy, sec-butoxy, tert-butoxy, and the like. 4 may be a substituted or unsubstituted 5- or 6-membered cyclic alkoxy group such as -O-cyclopentyl and -O-cyclohexyl, a branched alkyl group having from 3 to 6 carbon atoms such as isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, neopentyl, or a substituted or unsubstituted 5- or 6-membered cyclic alkyl group such as cyclopentyl, methylcyclopentyl, cyclohexyl, and methylcyclohexyl.
[0052] Further preferably, R 5 and R 6 may be the same, and more preferably, the silane-based compound is 4 , R 5 and R 6 For example, the silane compound used as one of the monomers in the copolymerization to obtain the fluorocopolymer of the present invention may be one or more selected from the group consisting of vinyltriisopropoxysilane, allyltriisopropoxysilane, butenyltriisopropoxysilane and vinylphenyldimethoxysilane.
[0053] Furthermore, in one embodiment of the crosslinkable compound, the crosslinkable compound is an epoxide-based compound having at least one alkenyl group represented by the following formula 4:
[0054] [ka]
[0055] In the formula, R 7 is an alkenyl group having 2 to 5 carbon atoms, such as ethenyl and allyl, or a group of the formula -R 8 -OC(=O)-CR 9 =CH2(wherein, R 8 is an alkylene group having 1 to 5 carbon atoms, R 9 is hydrogen or methyl), for example, -CH2-OC(=O)-C(CH3)=CH2. Examples of epoxide-based compounds having at least one alkenyl group include allyl glycidyl ether, glycidyl acrylate, and glycidyl methacrylate.
[0056] The repeating unit in the fluorocopolymer resulting from the crosslinkable silane-based or epoxide-based compound having at least one alkenyl group may be contained in an amount of 0.2 to 10 mol%, preferably 1.2 to 8 mol%, more preferably 1.4 to 7 mol% based on the total amount of repeating units of all monomers constituting the fluorocopolymer.
[0057] When the fluoroolefin compound contains a compound represented by formula 1, the vinyl ether compound contains a compound represented by formula 2, and the crosslinkable compound contains a compound represented by formula 3 or formula 4, the effect of excellent adhesion to the adherend surface can be exerted due to high compatibility with the adhesion promoter described later.
[0058] In one embodiment, the fluorocopolymer has a weight average molecular weight of 10,000 to 350,000 daltons, preferably a weight average molecular weight of 50,000 to 350,000 daltons, more preferably a weight average molecular weight of 100,000 to 350,000 daltons, and even more preferably a weight average molecular weight of 120,000 to 330,000 daltons.
[0059] The fluorocopolymer of the present invention can be prepared according to known methods. In some embodiments, the monomers can be polymerized without the use of a solvent, and in some embodiments, the monomers can be polymerized in a solvent for the fluorocopolymer or in a solvent for a non-fluorocopolymer. In other embodiments, the fluorocopolymer can be prepared by emulsion polymerization of the monomers. To prepare the desired fluorocopolymer, the monomers, one or more free radical initiators, and optionally, an acid acceptor are charged into an autoclave and heated at a pressure ranging from atmospheric pressure to as high as 1,500 atm and at a temperature ranging from 25°C to about 200°C for 10 minutes to 24 hours. The resulting product is then removed from the autoclave, filtered, rinsed, and dried to obtain the fluorocopolymer.
[0060] Suitable free radical initiators used in the polymerization process for preparing fluorocopolymers may be any known azo and / or peroxide initiator. For example, di(4-t-butylcyclohexyl)dicarbonate, di-t-butyl peroxide, acetyl peroxide, lauroyl peroxide, benzoyl peroxide, 2,2-azodiazobutyronitrile, 2,2-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl-2,2-azobis(isobutyrate) or combinations thereof may be used. The amount of free radical initiator that may be used ranges from 0.05 to 4 parts by weight based on 100 parts by weight of total monomers in the monomer mixture. In other embodiments, the amount of free radical initiator used ranges from 0.1 to 3.5 parts by weight, and in further embodiments, the amount of free radical initiator used ranges from 0.2 to 3.25 parts by weight.
[0061] An acid acceptor may also be used in the polymerization process to form the fluorocopolymer of the present invention. The acid acceptor may be a metal carbonate or metal oxide, such as sodium carbonate, calcium carbonate, potassium carbonate, magnesium carbonate, barium oxide, calcium oxide, magnesium oxide, or a combination thereof. The amount of the acid acceptor may range from 0 to 5 parts by weight based on 100 parts by weight of the total monomers in the monomer mixture. In other embodiments, the amount of the acid acceptor may range from 0.1 to 4 parts by weight, and in additional embodiments, the amount of the acid acceptor may range from 0.2 to 3 parts by weight. The acid acceptor may be present in the fluoroolefin compound or may be present to neutralize acids such as hydrogen fluoride that may be generated during the polymerization process.
[0062] Next, the adhesion promoter will be described.
[0063] The adhesion promoter serves to significantly improve adhesion between the passivation layer and the surface to be adhered, particularly when the substrate is Au or silicon nitride, and enhances patternability.
[0064] In one embodiment, the adhesion promoter is a thiol-based adhesion promoter. In another embodiment, the adhesion promoter is a diol-based adhesion promoter. Examples of thiol-based adhesion promoters include sulfur-functional carboxylic acids, sulfur-functional alcohols, and sulfur-functional silanes. Specific examples of thiol-based adhesion promoters include 3-(triethoxysilyl)propanethiol (MPTES), 6-mercapto-1-hexanol, 3-mercaptopropionic acid, 11-mercapto-1-undecanol, and 3-(trimethoxysilyl)propanethiol (MPTMS). Examples of diol-based adhesion promoters include 1,n-hydrocarbon diols, where n corresponds to 2 to 6 carbon hydrocarbons, and alkyl-substituted 1,2-benzenediols. Specific examples of diol-based adhesion promoters include 4-tert-butylbenzene-1,2-diol, hexane-1,6-diol, and 1,3-butylene glycol.
[0065] In one embodiment, the adhesion promoter comprises a first adhesion promoter containing a thiol-based adhesion promoter and a second adhesion promoter containing a diol-based adhesion promoter. In this embodiment, the effect of adhesion to the adherend surface and pattern formability is remarkably excellent. In one embodiment, the first adhesion promoter comprises one or more selected from the group consisting of 3-(triethoxysilyl)propanethiol (MPTES), 6-mercapto-1-hexanol, 3-mercaptopropionic acid, 11-mercapto-1-undecanol, and 3-(trimethoxysilyl)propanethiol (MPTMS), preferably 3-(triethoxysilyl)propanethiol (MPTES), and the second adhesion promoter comprises one or more selected from the group consisting of 4-tert-butylbenzene-1,2-diol, hexane-1,6-diol, and 1,3-butylene glycol, preferably 4-tert-butylbenzene-1,2-diol. When the first adhesion promoter and the second adhesion promoter each contain a preferred material, this can be very advantageous in terms of adhesion to the adherend surface and pattern formability.
[0066] In one embodiment, the weight ratio of the first adhesion promoter to the second adhesion promoter is 1:0.5 to 3.5, preferably 1:1 to 2.5. If the weight ratio of the first adhesion promoter to the second adhesion promoter is less than 1:0.5 or more than 1:3.5, the adhesion between the passivation layer and the adherend surface cannot be improved to a desired level, and pattern formability may be reduced.
[0067] The adhesion promoter may be contained in an amount of 0.5 to 3.5 parts by weight, preferably 1 to 2.5 parts by weight, per 100 parts by weight of the fluorocopolymer. If the adhesion promoter is less than 0.5 parts by weight per 100 parts by weight of the fluorocopolymer, the adhesion between the passivation layer and the adherend surface cannot be improved to a desired level, and pattern formability may be reduced. If the adhesion promoter is more than 3.5 parts by weight, peeling of the passivation layer may occur, the stability of the composition may be reduced, and pattern formability may be reduced.
[0068] The composition for forming a passivation layer according to the present invention may further contain a photoacid generator.
[0069] The photoacid generator may be any photoacid generator commonly used in the art, without any limitation. Preferred examples of the photoacid generator include (p-isopropylphenyl)(p-methylphenyl)iodonium tetrakis(pentafluorophenyl)borate, tris[4-(4-acetylphenyl)sulfanylphenyl]sulfonium tris(trifluoromethanesulfonyl)methide, bis(1,1-dimethylethylphenyl)iodonium salt having tris[(trifluoromethane)sulfonyl]methane or bis(4-decylphenyl)iodonium hexafluoroantimonate oxirane, 4,4',4''-tris(t-butylphenyl)sulfonium triflate, 4,4'-di-t-butylphenyl The compound may contain one or more selected from the group consisting of arylphenyliodonium triflate, diphenyliodonium tetrakis(pentafluorophenyl)sulfonium borate, triarylsulfonium tetrakis(pentafluorophenyl)borate, triphenylsulfonium tetrakis(pentafluorophenyl)sulfonium borate, 4,4'-di-t-butylphenyliodonium tetrakis(pentafluorophenyl)borate, tris(t-butylphenyl)sulfonium tetrakis(pentafluorophenyl)borate, and 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate.
[0070] Here, the photoacid generator may be further contained in an amount of 0.1 to 5 parts by weight, preferably 0.1 to 2 parts by weight, more preferably 0.1 to 1.5 parts by weight, and even more preferably 0.2 to 1 part by weight, based on 100 parts by weight of the fluorocopolymer.
[0071] Furthermore, the composition for forming a passivation layer according to the present invention may further contain a photosensitizer.
[0072] The photosensitizer may be any photosensitizer commonly used in the art, without any limitations, and may preferably contain one or more selected from the group consisting of chrysene, benzpyrene, fluoranthene, pyrene, anthracene, phenanthrene, xanthone, indanthrene, thioxanthen-9-one, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 1-chloro-4-propoxythioxanthone, and phenothiazine.
[0073] The photosensitizer may be optionally further included in the composition for preparing the passivation layer, i.e., may be included in an amount of 0 to 10 parts by weight, preferably 0.05 to 5 parts by weight, more preferably 0.1 to 2 parts by weight, and even more preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the fluorocopolymer.
[0074] Furthermore, the composition for forming a passivation layer of the present invention may further contain a solvent.
[0075] The composition for forming a passivation layer containing a fluorocopolymer may further contain 150 to 450 parts by weight, preferably 200 to 450 parts by weight, more preferably 250 to 450 parts by weight, of a solvent relative to 100 parts by weight of the fluorocopolymer so that the composition for forming a passivation layer containing the fluorocopolymer forms a suitable passivation layer on a surface to be adhered by a predetermined application method.
[0076] The fluoropolymer may also be present in the passivation layer-making composition in a dissolved state in the solvent. Here, "dissolved" means that the fluoropolymer is dissolved in the solvent and no solid or gel-like fluoropolymer visible to the naked eye remains suspended in the solvent. The passivation layer-making composition is formed in a conventional manner using conventional equipment. For example, the solvent can be added to a stirring vessel and then the fluoropolymer can be added to the desired content. The mixture may be stirred, optionally with heating, until the fluoropolymer is dissolved in the solvent.
[0077] According to one embodiment of the present invention, the composition for forming a passivation layer is filtered under a predetermined pressure using a cartridge filter having a pore size of micrometers or submicrometers (e.g., 0.4 to 4 μm or 1.5 μm), thereby removing particles having a particle size of more than 0.4 μm from the composition for forming a passivation layer. That is, a small amount of particles having a particle size of more than 0.4 micrometers but less than 1 micrometer may pass through the filter. Therefore, there may be cases where particles having a particle size of more than 1 μm are substantially absent in the composition for forming a passivation layer.
[0078] The solvent that may be included in the composition for forming a passivation layer according to the present invention may be any material that is capable of dissolving the fluorocopolymer and forming a phase-stable composition under ambient conditions.
[0079] According to one embodiment of the present invention, the solvent may have a normal boiling point of 50° C. or higher, preferably 100° C. or higher, preferably 150° C. or higher, but the present invention is not limited thereto.
[0080] The solvent may be any solvent commonly used in the art without limitation, and may preferably include one or more selected from the group consisting of acetone, acetylacetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, 2-pentanone, 3-pentanone, 2-heptanone, 3-heptanone, cyclopentanone, cyclohexanone, ethyl acetate, propyl acetate, butyl acetate, isobutyl acetate, pentyl acetate, cyclohexyl acetate, heptyl acetate, ethyl propionate, propyl propionate, butyl propionate, isobutyl propionate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, methyl lactate, ethyl lactate, gamma-butyrolactone, diisopropyl ether, dibutyl ether, ethyl propyl ether, anisole, dichloromethane, chloroform, and tetrachloroethylene.
[0081] According to another embodiment of the present invention, the solvent may be a non-reactive solvent, meaning that the solvent is not a component of the ultimately produced passivation layer.
[0082] The present invention also provides a passivation layer formed by crosslinking the composition for producing a passivation layer of the present invention by light and heat, the composition for producing a passivation layer comprising a fluorocopolymer, which is a random copolymer formed by randomly copolymerizing the above-mentioned fluoroolefin compound, vinyl ether compound and crosslinkable compound, and an adhesion promoter.
[0083] At least a portion of the passivation layer according to the present invention can then be developed to form a predetermined pattern.
[0084] Furthermore, the passivation layer according to the present invention may have a peeled area of less than 6% of the lattice area, preferably less than 5% of the lattice area, in an adhesion evaluation measured by the following measurement method 1.
[0085] Measurement method 1 The passivation layer of the Au substrate on which the passivation layer has been formed is cross-cut so that there are 100 graduations at 1 mm intervals, and the adhesion is evaluated in accordance with ASTM D3359.
[0086] When the peeled area in the adhesion evaluation exceeds 6% of the lattice area, the adhesion is considered to be poor.
[0087] Furthermore, the passivation layer according to the present invention may have a dielectric constant, measured at a frequency of 1 MHz in accordance with ASTM D150, of 2.65 F / m or less, preferably 2.6 F / m or less, and more preferably 2.58 F / m or less.
[0088] Additionally, the passivation layer of the present invention may have a water absorption rate of 0.15% or less, preferably 0.13% or less, as measured by Equation 1 below.
[0089] equation 1 Water absorption rate (%)=((W2-W1) / W1)×100(%) Here, W1 is the weight of the passivation layer before being left for 24 hours under conditions of a temperature of 85°C and a relative humidity of 85%, and W2 is the weight of the passivation layer after being left for 24 hours under conditions of a temperature of 85°C and a relative humidity of 85%.
[0090] In the following, a method for forming a passivation layer on a substrate will be described as an example of a method for forming a passivation layer on an adherend surface using the composition for forming a passivation layer according to the present invention, but this method is merely one example and is not intended to be limiting.
[0091] The passivation layer may be formed on various substrates including conductive, semiconductive and / or nonconductive materials. For example, the substrate may be one or more selected from the group consisting of glass, polymer, inorganic semiconductor, organic semiconductor, tin oxide, zinc oxide, titanium dioxide, silicon dioxide, indium oxide, indium zinc oxide, zinc tin oxide, indium gallium oxide, indium gallium zinc oxide, indium tin zinc oxide, cadmium sulfide, cadmium selenide, silicon nitride, gold, copper and aluminum, and preferably silicon nitride or gold.
[0092] The method for forming a passivation layer on a substrate using the composition for forming a passivation layer may include a step (1) of treating at least a part of the substrate with the composition for forming a passivation layer.
[0093] The treatment with the composition can be carried out by conventional methods such as spin coating, spray coating, flow coating, curtain coating, roller coating, brushing, inkjet printing, screen printing, offset printing, gravure printing, flexographic printing, lithographic printing, dip coating, blade coating or drop coating. Spin coating involves applying an excess amount of the composition for making a passivation layer to the substrate, and then rotating the substrate at high speed to spread and distribute the composition evenly over the entire surface of the substrate by centrifugal force. The thickness of the resulting passivation layer can depend on the spin coating speed, the concentration of the composition for making a passivation layer, and the solvent used.
[0094] Furthermore, the method may include a step (2) of removing at least a portion of the solvent from the composition for forming a passivation layer that has been applied onto at least a portion of the substrate.
[0095] After treating the substrate with the composition for forming a passivation layer, at least a portion of the solvent, or preferably substantially all of it, can be removed by exposing the substrate to a predetermined temperature and a pressure less than atmospheric pressure, or by blowing a gas directly or indirectly onto the treated composition for forming a passivation layer, or by using a combination of these methods.
[0096] For example, the composition processed to create the passivation layer may be heated in air or, optionally, in a vacuum oven with a small nitrogen gas purge. In other embodiments, the composition processed to create the passivation layer may be heated to a temperature in the range of 60 to 110° C. to remove the solvent.
[0097] Furthermore, the method includes a step (3) of forming a crosslinked passivation layer. In the crosslinking, the fluoropolymer can be considered to be a crosslinkable fluoropolymer, and means a crosslinkable uncrosslinked fluoropolymer. For example, the fluoropolymer may be a photo / thermal crosslinkable fluorocopolymer, in which when irradiated with light of a predetermined wavelength in the presence of one or more of a photoacid generator and a photosensitizer, a part of the uncrosslinked fluoropolymer is photocrosslinked, for example, the epoxide contained in the fluorocopolymer undergoes a ring-opening reaction by photoirradiation, and the composition is crosslinked.
[0098] In one embodiment, the step of forming a passivation layer by crosslinking the fluorocopolymer comprises forming the passivation layer by photo- and / or thermal crosslinking of the fluorocopolymer. In one embodiment, the crosslinks between the fluorocopolymer substituents resulting from the silane-based or epoxide-based compounds are formed as a result of photo- and thermal action.
[0099] Furthermore, the composition for producing a passivation layer according to the present invention and the passivation layer formed using the same can simultaneously exhibit effects such as a low dielectric constant, a low water absorption rate, excellent pattern formability, and excellent adhesion to the surface to be adhered, and as a result, can be widely applied to various products such as thin film transistors, organic field effect transistors, semiconductors, semiconductor oxide field effect transistors, integrated circuits, light emitting diodes, bank layers containing organic light emitting diodes, display devices, printed circuit boards, and photovoltaic elements.
[0100] The present invention will now be described in more detail with reference to the following examples, which should not be construed as limiting the scope of the present invention, but should be construed to facilitate understanding of the present invention. EXAMPLES
[0101] Example 1 (1) Preparation of Fluorocopolymer In a 400 ml autoclave cooled to a temperature of −25° C., 0.5 g of powdered potassium carbonate (PX1390-1, EMD Millipore), 0.24 g of dimethyl 2,2′-azobisisobutyrate (V-601, Fujifilm Wako Pure Chemical Industries, Ltd.), 3.8 mL (4.4 g) of a silane-based compound (SIV9210, Gelest, Inc.) which is a compound represented by the following formula 3, 36 g (0.5 mol) of a vinyl ether-based compound (A15691-0F, Alfa Aesar) which is a compound represented by the following formula 2, and 200 mL (250 g) of 1,1,1,3,3-pentafluorobutane (H33737, Alfa Aesar) are placed. The autoclave is then evacuated, and 50 g (0.5 mol) of a fluoroolefin-based compound which is a compound represented by the following formula 1 is placed in the autoclave. The resulting reaction mixture is shaken and heated to 66°C. The pressure inside the autoclave peaks at 200 psig and drops to 76 psig after 8 hours. During cooling, a viscous liquid (233.85 g) is obtained. The product is purged with nitrogen for about 3 days and then further dried in a vacuum oven at 74°C for 19 hours to prepare the fluorocopolymer.
[0102] [ka]
[0103] R 1 is F in formula 1, and R 2 is a linear alkyl group having two carbon atoms (ethyl group) in formula 2, and R 3 is a vinyl group, and R 4 , R 5 and R 6 were branched alkoxy groups each having 3 carbon atoms (isopropoxy groups).
[0104] (2) Preparation of composition for forming passivation layer 29.75g of the fluorocopolymer prepared above is mixed with 69.41g of propylene glycol monomethyl ether acetate (PGMEA) as a solvent, and stirred for 6 hours until the fluorocopolymer is dissolved. Then, 0.13g of 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate as a photoacid generator, 0.07g of 2-isopropylthioxanthone as a photosensitizer, and 0.45g of an adhesion promoter (1.51 parts by weight per 100 parts by weight of the fluorocopolymer) containing 3-(triethoxysilyl)propanethiol (MPTES) as a first adhesion promoter and 4-tert-butylbenzene-1,2-diol as a second adhesion promoter in a weight ratio of 1:1.5 are mixed in sequence, and stirred for 2 hours to prepare a composition for making a passivation layer.
[0105] (3) Formation of a passivation layer The above-prepared composition for forming a passivation layer is spin-coated on an Au substrate at 2000 rpm (revolutions per minute), and then heat-treated on a hot plate at 90°C for 3 minutes to form a coating layer with a thickness of 7 μm. The substrate on which the coating layer is formed is then covered with a mask printed with a chrome pattern, and the substrate is then exposed to a high-pressure mercury lamp (i, g, h rays) with an output of 15 mW / cm in a mask aligner. 2 The substrate is exposed to UV light generated by UV irradiation for 20 seconds. Then, a post-heat treatment is performed at a temperature of 80°C for 2 minutes, followed by puddle development at 23°C for 4 minutes with propylene glycol monomethyl ether acetate as a developer. Finally, the substrate is baked in a nitrogen-purged oven at 230°C for 2 hours to produce a substrate having a passivation layer with a thickness of 6 μm and a square pattern of 25 μm wide and 25 μm long.
[0106] Examples 2 to 14 and Comparative Examples The passivation layers shown in Tables 1 to 3 were prepared in the same manner as in Example 1, except that conditions such as the weight ratio and type of the first adhesion promoter and the second adhesion promoter contained in the adhesion promoter contained in the composition for preparing a passivation layer, whether the first adhesion promoter and the second adhesion promoter are each included, the total content of the adhesion promoters, and whether an adhesion promoter is included were changed.
[0107] Experimental Example 1 The substrates on which the passivation layers were formed, produced in the examples and comparative examples, were evaluated for the following properties, and the results are shown in Tables 1 to 4.
[0108] 1.Adhesion evaluation For the substrates having the passivation layer produced in the Examples and Comparative Examples, the passivation layer of each test piece is cut into a grid pattern using a cutter so that the scale number is 100 at 1 mm intervals in accordance with the ASTM D3359 method. Next, adhesive tape is applied, and the adhesion state of the passivation layer after the adhesive tape is peeled off is confirmed and classified as follows: 5B to 0B. 5B: The edges of the cut were completely smooth and none of the grid squares peeled off. 4B: Small pieces of coating were peeled off at the intersections, less than 5% of the area was affected. 3B: Small pieces of coating were peeled off at intersections along the edges, with the affected area being greater than 5% but less than 15% of the grid. 2B: The coating is torn thinly along the edges or grids, with the affected area being greater than 15% but less than 35% of the grid. 1B: The coating has delaminated along the edges and grids, with entire grids delaminating and the affected area being greater than or equal to 35% but less than 65% of the grid. 0B: The entire square was peeled off such that the affected area was 65% or more of the grid.
[0109] 2. Evaluation of pattern formation The pattern formability of the patterns formed on the substrates having the passivation layers prepared in the Examples and Comparative Examples is evaluated by an optical microscope. Here, the pattern formability is evaluated as follows: ◎ when all patterns are formed with a width of 25 μm and a length of 25 μm, ○ when the pattern formed with a width of 25 μm and a length of 25 μm is 50 to 80% of the whole pattern due to partial peeling or not being developed, △ when the pattern formed with a width of 25 μm and a length of 25 μm is 20 to 50% of the whole pattern due to partial peeling or not being developed, and X when no pattern is formed due to all coating being peeled off.
[0110] 3.Evaluation of dielectric constant The passivation layers prepared in the examples and comparative examples were formed on conductive substrates such as Au and Ag, and the dielectric constants at a frequency of 1 MHz were evaluated using the dielectric bridge method (ASTM D150).
[0111] 4.Evaluation of water absorption rate The substrates on which the passivation layers prepared in the Examples and Comparative Examples were formed were left for 24 hours under constant temperature and humidity conditions, i.e., a temperature of 85°C and a relative humidity of 85%, and then the water absorption rate was evaluated according to the following equation 1 using a method of measuring the weight change before and after the substrate absorbs moisture under constant temperature and humidity conditions.
[0112] equation 1 Water absorption rate (%)=((W2-W1) / W1)×100(%) Here, W1 is the weight of the passivation layer before being left for 24 hours under conditions of a temperature of 85°C and a relative humidity of 85%, and W2 is the weight of the passivation layer after being left for 24 hours under conditions of a temperature of 85°C and a relative humidity of 85%.
[0113] [Table 1]
[0114] [Table 2]
[0115] [Table 3]
[0116] From Tables 1 to 3, it can be seen that Examples 1, 3, 4, 7 and 8, which satisfy all of the conditions such as the weight ratio and type of the first adhesion promoter and the second adhesion promoter contained in the adhesion promoter contained in the composition for producing a passivation layer of the present invention, whether or not the first adhesion promoter and the second adhesion promoter are contained, respectively, the total content of the adhesion promoters, and whether or not an adhesion promoter is contained, can simultaneously exhibit effects such as significantly superior adhesion to the adherend surface and pattern formability, as well as low dielectric constant and low water absorption, compared to Examples 2, 5, 6, 9 to 14 and the comparative examples which do not satisfy any of the above-mentioned conditions.
[0117] Although specific embodiments of the present invention have been described, it should be understood that the technical idea of the present invention is not limited to the described embodiments, and that other embodiments may be made within the scope of the same or equivalent technical idea by those skilled in the art to which the present invention pertains by adding, modifying, deleting, and supplementing elements.
Claims
1. A composition for making a passivation layer, comprising: A fluorocopolymer which is a random copolymer of monomers including a fluoroolefin-based compound, a vinyl ether-based compound, and a crosslinkable compound selected from the group consisting of a silane-based compound having at least one alkenyl group and an epoxide-based compound having at least one alkenyl group; and a diol adhesion promoter.
2. The fluoroolefin-based compound is a compound represented by the following formula 1, the vinyl ether-based compound is a compound represented by the following formula 2, and the crosslinkable compound is a silane-based compound having at least one alkenyl group represented by the following formula 3, 【Chemistry 1】 In formula 1, R 1 is a linear perfluoroalkoxy group having 1 to 5 carbon atoms, a branched perfluoroalkoxy group having 3 to 5 carbon atoms, a linear perfluoroalkyl group having 1 to 3 carbon atoms, H, F, or Cl; In formula 2, R 2 is a linear alkyl group having 1 to 6 carbon atoms, a branched alkyl group having 3 to 6 carbon atoms, a cyclic alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted aryl group; In formula 3, R 3 is an ethylenically unsaturated hydrocarbon group, R 4 is an aryl, an aryl-substituted hydrocarbon group, a branched alkoxy group, a substituted or unsubstituted cyclic alkoxy group, a branched alkyl group, or a substituted or unsubstituted 5- or 6-membered cyclic alkyl group; R 5 and R 6 The composition of claim 1 , wherein is independently selected from a linear or branched alkoxy group, or a substituted or unsubstituted cyclic alkoxy group.
3. The fluoroolefin-based compound is a compound represented by the following formula 1, the vinyl ether-based compound is a compound represented by the following formula 2, and the crosslinkable compound is a silane-based compound having at least one alkenyl group represented by the following formula 3, 【Chemistry 2】 In formula 1, R 1 is a linear perfluoroalkoxy group having 1 to 5 carbon atoms, a branched perfluoroalkoxy group having 3 to 5 carbon atoms, a linear perfluoroalkyl group having 1 to 3 carbon atoms, H, F, or Cl; In formula 2, R 2 is a linear alkyl group having 1 to 6 carbon atoms, a branched alkyl group having 3 to 6 carbon atoms, a cyclic alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted aryl group; In formula 3, R 3 is an ethylenically unsaturated hydrocarbon group having 2 to 5 carbon atoms, R 4 2. The composition of claim 1, wherein R is an aryl, an aryl-substituted hydrocarbon group, a branched alkoxy group having 3 to 6 carbon atoms, a substituted or unsubstituted 5- or 6-membered cyclic alkoxy group, a branched alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted 5- or 6-membered cyclic alkyl group, and R5 and R6 are independently selected from a linear or branched alkoxy group having 1 to 6 carbon atoms, or a substituted or unsubstituted 5- or 6-membered cyclic alkoxy group.
4. The fluoroolefin-based compound is a compound represented by the following formula 1, the vinyl ether-based compound is a compound represented by the following formula 2, and the crosslinkable compound is an epoxide-based compound having at least one alkenyl group represented by the following formula 4, 【Chemistry 3】 【Chemistry 4】 In formula 1, R 1 is a linear perfluoroalkoxy group having 1 to 5 carbon atoms, a branched perfluoroalkoxy group having 3 to 5 carbon atoms, a linear perfluoroalkyl group having 1 to 3 carbon atoms, H, F, or Cl; In formula 2, R 2 is a linear alkyl group having 1 to 6 carbon atoms, a branched alkyl group having 3 to 6 carbon atoms, a cyclic alkyl group having 3 to 6 carbon atoms, or a substituted or unsubstituted aryl group; In formula 4, R 7 is an alkenyl group having 2 to 5 carbon atoms, or a group of the formula -R 8 -OC(=O)-CR 9 =CH 2 In the formula, R 8 is an alkylene group having 1 to 5 carbon atoms, R 9 The composition of claim 1 , wherein is hydrogen or methyl.
5. 2. The composition of claim 1, wherein the diol adhesion promoter is selected from the group consisting of 1,n-hydrocarbon diols, where n is from 2 to 6, and alkyl substituted 1,2-benzene diols.
6. The composition of claim 1, wherein the diol adhesion promoter is selected from the group consisting of 4-tert-butylbenzene-1,2-diol, hexane-1,6-diol, and 1,3-butylene glycol.
7. The composition of claim 1, further comprising a thiol-based adhesion promoter.
8. 8. The composition of claim 7, wherein the thiol based adhesion promoter is selected from the group consisting of sulfur functional carboxylic acids, sulfur functional alcohols, and sulfur functional silanes.
9. 8. The composition of claim 7, wherein the thiol adhesion promoter is selected from the group consisting of 3-(triethoxysilyl)propanethiol (MPTES), 6-mercapto-1-hexanol, 3-mercaptopropionic acid, 11-mercapto-1-undecanol, and 3-(trimethoxysilyl)propanethiol (MPTMS).
10. 8. The composition of claim 7, wherein the thiol adhesion promoter is one or more selected from the group consisting of sulfur-functional carboxylic acids, sulfur-functional alcohols, and sulfur-functional silanes, and the diol adhesion promoter is one or more selected from the group consisting of 1,n-hydrocarbon diols, where n is from 2 to 6, and alkyl-substituted 1,2-benzene diols.
11. The composition according to claim 7, wherein the thiol-based adhesion promoter is one or more selected from the group consisting of 3-(triethoxysilyl)propanethiol (MPTES), 6-mercapto-1-hexanol, 3-mercaptopropionic acid, 11-mercapto-1-undecanol, and 3-(trimethoxysilyl)propanethiol (MPTMS), and the diol-based adhesion promoter is one or more selected from the group consisting of 4-tert-butylbenzene-1,2-diol, hexane-1,6-diol, and 1,3-butylene glycol.
12. 8. The composition of claim 7, wherein the weight ratio of said thiol based adhesion promoter to said diol based adhesion promoter is 1:0.5 to 3.
5.
13. 10. The composition of claim 1 comprising from 0.5 to 3.5 parts by weight of said diol adhesion promoter per 100 parts by weight of said fluorocopolymer.
14. 10. The composition of claim 1 further comprising 0.1 to 5 parts by weight of a photoacid generator (PAG) per 100 parts by weight of said fluorocopolymer.
15. The composition of claim 1 further comprising from 150 to 450 parts by weight of a solvent per 100 parts by weight of said fluorocopolymer.
16. 10. The composition of claim 1, further comprising 0.05 to 5 parts by weight of a photosensitizer (PS) per 100 parts by weight of said fluorocopolymer.
17. 11. A passivation layer comprising a layer of a crosslinked coating composition disposed on an exterior surface of a semiconductor device, the coating composition comprising the composition of claim 1.
18. 20. The passivation layer of claim 17, wherein at least a portion of the passivation layer is developed to form a predetermined pattern.
19. 20. The passivation layer of claim 17, wherein the exterior surface of a semiconductor device comprises at least one substrate selected from the group consisting of a conductive material, a semiconductive material, and a non-conductive material.
20. 20. The passivation layer of claim 17, wherein the exterior surface of a semiconductor device comprises at least one substrate selected from the group consisting of glass, polymer, inorganic semiconductor, organic semiconductor, tin oxide, zinc oxide, titanium dioxide, silicon dioxide, indium oxide, indium zinc oxide, zinc tin oxide, indium gallium oxide, indium gallium zinc oxide, indium tin zinc oxide, cadmium sulfide, cadmium selenide, silicon nitride, gold, copper, and aluminum.
21. 20. The passivation layer of claim 17, wherein the exterior surface of a semiconductor device comprises at least one substrate selected from the group consisting of silicon nitride and gold.
22. 18. The passivation layer according to claim 17, wherein the peeled area is less than 6% of the lattice area when evaluated for adhesion by the following measurement method 1, the dielectric constant is 2.65 or less when measured at a frequency of 1 MHz according to ASTM D150, and the water absorption is 0.15% or less when measured by the following equation 1: [Measurement method 1] The passivation layer of the Au base material on which the passivation layer is formed is cross-cut to give 100 marks at 1 mm intervals, and the adhesion is evaluated in accordance with ASTM D3359. [Equation 1] Water absorption rate (%) = ((W 2 -W 1 ) / W 1 )×100(%) During the ceremony, W 1 is the weight of the passivation layer before being left for 24 hours under conditions of a temperature of 85° C. and a relative humidity of 85%, and W 2 is the weight of the passivation layer after being left for 24 hours under conditions of a temperature of 85° C. and a relative humidity of 85%.
Citation Information
Patent Citations
The composition for fluororesin coating method for coating
JP1975145431A
Fluorine-based coating compound
JP1991212464A
Curable resin composition and resin cured product
JP2001089625A
Protective layer containing photocrosslinked fluoropolymer
JP2017525785A
functionalized fluorinated copolymer
JP2018532028A